Innovative Utilization of Orange Peel Waste through Modified Citrus Pectin (MCP) as a Preventive Agent Against Atherosclerosis Progression via Galectin-3 (Gal-3) Inhibition: A Comprehensive Literature Review on In Vitro and In Vivo Study Designs - Nursyafi, Fauzan Syarif; Febrian, Lamirza Rasyid Mikzy; Putra, Rivaldi Dwi; Renato, Hagil Alghufron; Kurniawan, Dio (Rumah Jurnal, 2024)
Atherosclerosis is an arterial disease often associated with lipids and other metabolic alterations. Various factors are involved in developing atherosclerosis, including Galectin-3 (Gal-3). Pre-clinical studies have shown that Modified Citrus Pectin (MCP), a modified polysaccharide from citrus peels, has the potential of inhibiting Gal-3 and countering the development of atherosclerosis. Thus, this review aims to analyze the role of MCP on inhibiting and regulating Galectin-3 (Gal-3) as an alternative therapeutic target. We examined valid pre-clinical experimental study designs taken from the databases Science Direct, Taylor & Francis, PubMed, and Google Scholar, with publication dates ranging from 2014 to 2024. 15 research articles meet the established inclusion criteria. Our review found that Gal-3 levels rose during atherosclerosis development, triggering proteins that disturbs cardiovascular physiology. Additionally, Gal-3 targeted inhibition using MCP has shown to have therapeutic effects that alleviates hypertrophy and plaque’s size. In essence, MCP emerges as a promising alternative therapy targeting Gal-3 in atherosclerosis progression.